Apalutamide: a better option for the treatment of non-metastatic castration resistant prostatic carcinoma - Ranjan, Raushan Kumar; Chandra, Akash (International Journal of Basic & Clinical Pharmacology, 2018)
Prostate cancer is cancer of the prostate, a gland in the male reproductive system. Most prostate cancers are slow growing; however, some grow relatively quickly. The cancer cells may spread from the prostate to other area of the body, particularly the bones and lymph nodes. Factors that increase the risk of prostate cancer include older age, a family history of the disease, and race. About 99% of cases occur in males over the age of 50. Clinical features include hematuria, dysuria (painful urination),nocturia(urination at night). Lower blood levels of vitami D may increase the risk of developing prostate cancer. Infection with the sexually transmitted diseases, chlamydia, gonorrhea, syphilis and prostatitis seem to increase risk of prostate cancer. Diagnosis can be confirmed by digital rectal examination (DRE) with prostate-specific antigen (PSA) blood test, cystoscopy, transrectal ultrasonography and biopsy (The removal of small pieces of the prostate for microscopic examination). Medicines like 5-alpha-reductase inhibitors (finasteride and dutasteride) reduce the overall risk of prostate cancer. Apalutamide, sold under the brand name Erleada, is a nonsteroidal antiandrogen (NSAA) medication which is used in the treatment of prostate cancer. It is specifically indicated for use in conjunction with castration in the treatment of non-metastatic castration-resistant prostate cancer (NM-CRPC). It is taken by mouth. Apalutamide was first described in 2007 and was approved for the treatment of prostate cancer in February 2018. Apalutamide is used in conjunction with castration, either via bilateral orchiectomy or gonadotropin-releasing hormone analogue (GnRH analogue) therapy, as a method of androgen deprivation therapy in the treatment of non-metastatic castration-resistant prostate cancer (NM-CRPC).